Resolution of a Dispute Over Inherited Land Sold in Lubuk Basung Subdistrict, Agam Regency (Study of Judgment No. 893 K/Pdt/2025) - Ahmad Akbar; Syofiaty Lubis (IHSA Institute, 2026)
This research aims to analyze the legal position of high inheritance property (harato pusako tinggi) under Minangkabau customary law and the resolution process of disputes arising from the unilateral sale of such property without the approval of the clan, as reflected in Decision Number 893 K/Pdt/2025 in Lubuk Basung District, Agam Regency. This study employs a normative juridical research method using a case approach by examining court decisions, legislation, and relevant legal literature. The results show that harato pusako tinggi is a communal hereditary property passed down through generations and cannot be transferred or sold without the consent of all clan members. The dispute in this case arose because one party sold pusako tinggi land without the approval of the clan, thereby violating Minangkabau customary law. The dispute resolution process was carried out through litigation, beginning from the District Court up to the Supreme Court. In its decision, the court recognized the existence and application of customary law by declaring the actions of Defendant I unlawful and ordering the return of the land rights to the clan through the Mamak Kepala Waris. Furthermore, this research finds that the settlement process did not fully prioritize customary dispute resolution mechanisms based on the Minangkabau principle of “bajanjang naiak, batanggo turun.” Therefore, strengthening the role of customary institutions and ninik mamak, optimizing non-litigation dispute resolution, and harmonizing customary law with national law are necessary to prevent similar disputes in the future